Epidemiology of Frequent Visits to the Emergency Department at a Tertiary Care Hospital in Saudi Arabia: Rate, Visitors’ Characteristics, and Associated Factors - Al-Surimi K; Yenugadhati N; Shaheen N; Althagafi M; Alsalamah M (International Journal of General Medicine, 2021)
Khaled Al-Surimi,1– 3 Nagarajkumar Yenugadhati,1,2 Naila Shaheen,2,4 Majed Althagafi,1,2,5 Majid Alsalamah1,2,5 1College of Public Health and Health Informatics, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi Arabia; 2King Abdullah International Medical Research Center, Riyadh, Kingdom of Saudi Arabia; 3Faculty of Medicine and Health Sciences, Thamar University, Dhamar, Yemen; 4King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi Arabia; 5Department of Emergency Medicine, College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Naila ShaheenDepartment of Biostatistics and Bioinformatics, King Abdullah International Medical Research Center, King Saud Bin Abdulaziz University for Health Sciences, Ministry of National Guard-Health Affairs, P.O. Box 22490, Mail Code 1515, Riyadh, 11426, Kingdom of Saudi ArabiaTel +966-11-4294472Fax +966-11-4294466Email drnaila@hotmail.comBackground: Emergency department overcrowding is becoming a challenge for the healthcare management system globally and locally. This study aimed to estimate the frequency of ED visits, describe the patients’ profile along with visit-related characteristics, and associated factors in a tertiary care hospital.Methods: A retrospective cohort study was conducted at a tertiary care hospital. The study included patients age 14 years and above visiting the main emergency department in year 2013. Data were extracted from electronic medical records by a qualified data extraction team. Statistical analyses were performed, including the odds ratio and 95% confidence interval for the factors associated with highly frequent (≥ 14 visits) ED visits using logistic regression models.Results: There were 150,727 visits to the emergency department within a year. The number of frequent visitors was 7696 (9.38%), with 42,226 visits (28.01% of total ED visits). Highly frequent visitors totaled 249 (0.30%), with 5173 visits (3.43% of total ED visits). The frequent visitors’ average age was 42.55 (SD 20.14), and 48.99 (SD 21.33) for the highly frequent visitors’ group. More than half of the emergency visitors were females. The most common complaints among the highly frequent visitors were Gastrointestinal (21.34%), followed by Respiratory (13.47%), Orthopedic (12.57%), and Cardiovascular (12.43%). Multivariate analysis indicated that age, history of diabetes, history of cardiac diseases, insurance status, and nationality were significant predicators of highly frequent visits to the hospital emergency.Conclusion: Frequent and highly frequent visitors to emergency departments represent a significant proportion of adult patients presenting to ED. Their visits constitute almost one-third of total ED visits. Several factors associated with highly frequent ED visits have been identified. This study provides local empirical evidence to develop improvement policy and actions related to chronic issue of frequent and highly frequent visitation to hospital ED.Keywords: emergency department, frequent visits, hospital, quality improvement, Saudi Arabia